The invisible hour eaudiobook - Hoffman, Alice (Simon & Schuster Audio, 2023)
The latest New York Times bestseller from beloved author Alice Hoffman celebrates the enduring magic of books and is a "wonderful story of love and growth" (Stephen King). One June day when Mia Jacob can no longer see a way to survive, the power of words saves her. The Scarlet Letter was written almost two hundred years earlier, but it seems to tell the story of Mia's mother, Ivy, and their life inside the Community—an oppressive cult in western Massachusetts where contact with the outside world is forbidden. But how could this be? How could Nathaniel Hawthorne have so perfectly captured the pain and loss that Mia carries inside her? Through a journey of heartbreak, love, and time, Mia must abandon the rules she was raised with at the Community. As she does, she realizes that reading can transport you to other worlds or bring them to you, and that readers and writers affect one another in mysterious ways. She learns that time is more fluid than she can imagine, and that love is stronger than any chains that bind you. As a girl Mia fell in love with a book. Now as a young woman she falls in love with a brilliant writer as she makes her way back in time. But what if Nathaniel Hawthorne never wrote The Scarlet Letter ? And what if Mia Jacob never found it on the day she planned to die? From "the reigning queen of magical realism" (Kristin Hannah, New York Times bestselling author), this is the story of one woman's dream. For a little while it came true.